My choice - teaching in the field of fashion design: Maria de Jesus Faria Medeiros - Sant'Anna, Mara Rúbia (2020)
Dossier no. 6, which includes discussions about modeling, provided an opportu- nity for an interview with a teacher in the field who had a very diverse background and works at the Bachelor of Fashion at the Federal University of Piauí. His life trajectory begins in Fortaleza, through several educational institutions as a student and teacher, passes through other regions and projects in our country until he arrives in Teresina, where he continues to teach, research and make a difference. For all these reasons, she is inspiring for today’s new fashion professionals.